Technology as a Double-Edged Sword: Understanding Life Experiences and Coping With COVID-19 in India - Misra, Girishwar; Singh, Purnima; Ramakrishna, Madhumita; Ramanathan, Pallavi (Frontiers in Psychology, 2022)
The two waves of COVID-19 in India have had severe consequences for the lives of people. The Indian State-imposed various regulatory mechanisms like lockdowns, encouraged remote work, online teaching in academic institutions, and enforced adherence to the COVID protocols. The use of various technologies especially digital/ online technologies not only helped to adapt to the ‘new normal’ and cope with the disruptions in pursuing everyday activities but also to manage one’s well-being. However, the availability and accessibility of digital technologies to various sections of the population were not uniform across the various sections of society. This paper reports a series of 3 studies examining the nature of pandemic stress, the impact of technology use on people’s emotional well-being during turbulent times, and the effects of technology use on psychological resources like resilience, self-efficacy, motivation to work, and emotional well-being. The differences in the residential background (Urban/Rural) and SES (Low/High) in the extent of the use of technology and strength of psychological resources were assessed. The findings indicated that the most common causes of concern included worrying about family, friends, partners, fears of getting and giving the viral infection to someone; frustration and or boredom; and changes in normal sleep patterns. It was noted that technology was a double-edged sword and created barriers as well as opportunities for the people. Also, self-efficacy mediated the relationship between the use of technology and emotional wellbeing. The results have policy implications for building resilient communities in the post COVID period.